Anatomical Variations of the Paranasal Sinuses and the Nasal Cavity - Shrestha, Kundan Kumar; Acharya, K; Joshi, RR; Maharjan, S; Adhikari, D (Nepal Medical College Journal, 2019)
Computed tomography (CT) of the para-nasal sinuses (PNS) has nowadays become the investigation of choice for the diagnosis of sinonasal diseases. Numerous sinonasal anatomic variants exist and are frequently seen on CT scans. A sound knowledge of these variations is important not only for diagnosis but also for planning surgery in order to avoid complications. The aim of this study is to investigate the frequency of these variations in patients with sinonasal symptoms and also to determine their relation to sinonasal disease if any. A total of 76 patients were included in the study from August 2017 to July 2018 of which 43 (56.6%) were males and while 33 (43.4%) were females with male to female ratio of 1.3:1. The ages of patients ranged from 14 to 72 years with a mean age of 33.2±14.2 years. Out of 76 patients, 68 (89.5%) had at least one type of anatomical variation while 8 (10.5%) had no variation. Only one variation was seen in 39 (51.3%) patients while 29 (38.2%) had two or more variations. The most common variant was deviated nasal septum (DNS), occurring in 49 (64.5%) patients followed by concha bullosa (CB) and agger nasi cell (AN) seen in 15 (19.7%) and 14 (18.4%) patients respectively. Genderwise, anatomical variations were seen more in males but the difference was not statistically significant. Some variations were seen more on the right side while others on the left. Some variations were present bilaterally. The difference was not statistically significant. The presence of DNS was statistically significant in the study population (p value 0.012 in nonparametric chi square test). The age group 14 to 30 years showed maximum variations though not significant statistically. Therefore, during management of patients with sinonasal symptoms, these variations need to be addressed, if required, surgically. Proper knowledge of both common and uncommon sinonasal variations in our community could help in better surgical planning and overall management of sinonasal disorders.